Nanotechnology for CNS delivery of biological therapeutics - Amiji, Mansoor (Henry Stewart Talks, 2015)
Challenges of central nervous system (CNS) drug delivery, Strategies to enhance CNS delivery, O/W nanoemulsion for CNS delivery, Modulation of efflux transport with curcumin, Lipid modification of DALDA peptide, Nose to brain delivery of cyclosporine